Advanced Reconstruction of Vesicourethral Support (ARVUS) during Robot-assisted Radical Prostatectomy: One-year Functional Outcomes in a Two-group Randomised Controlled Trial - Student, Vladimir; Vidlar, Ales; Grepl, Michal; Hartmann, Igor; Buresova, Eva; Student, Vladimir (European urology, 2017)
BACKGROUND: The advent of robotics has facilitated new surgical techniques for radical prostatectomy. These allow adjustment of pelvic anatomical and functional relationships after removal of the prostate to ameliorate postprostatectomy incontinence (PPI) and reduce the time to complete continence. OBJECTIVES: To describe the results of a new surgical technique for reconstruction of vesicourethral anastomosis using the levator ani muscle for support during robot-assisted radical prostatectomy (RARP). DESIGN, SETTING, AND PARTICIPANTS: A prospective, randomised, single-blind study among 66 consecutive patients with localised prostate cancer (cT1-2N0M0) undergoing RARP from June to September 2014, 32 using the new technique and 34 using the standard posterior reconstruction according to Rocco. SURGICAL PROCEDURE: In the advanced reconstruction of vesicourethral support (ARVUS) intervention group, the fibres of the levator ani muscle, Denonvilliers fascia, retrotrigonal layer, and median dorsal raphe were used to form the dorsal support for the urethrovesical anastomosis. Suture of the arcus tendineus to the bladder neck served as the anterior fixation. MEASUREMENTS: We compared demographic data and preoperative and postoperative functional and oncologic results for the two groups. The primary endpoint was continence evaluated at different time points (24h, 2, 4, and 8 wk, and 6 and 12 mo). The secondary endpoints were perioperative and postoperative complications and erectile function. RESULTS AND LIMITATIONS: Using a continence definition of 0 pads/d, the continence rates for the ARVUS versus the control group were 21.9% versus 5.9% at 24h (p=0.079), 43.8% versus 11.8% at 2 wk (p=0.005), 62.5% versus 14.7% at 4 wk (p<0.001), 68.8% versus 20.6% at 8 wk (p<0.001), 75.0% versus 44.1% at 6 mo (p=0.013), and 86.66% versus 61.29% at 12 mo (p=0.04). International Index of Erectile Function questionnaire results at 6 and 12 mo after surgery showed similar potency rates for the control group (40.0% and 73.33%) and the ARVUS group (38.8% and 72.22%). There were four postoperative complications (2 in each group): three haematomas requiring transfusion and one lymphocele that needed drainage. No urinary retention, anastomosis leak, or perineal pain was observed. Limitations include the small sample size and the single-institution design. CONCLUSIONS: The ARVUS technique yielded better urinary continence results than standard posterior reconstruction, with no negative impact on erectile function, complication rate, or oncologic outcome. External validation is warranted before clear recommendations can be made. PATIENT SUMMARY: We showed that postprostatectomy incontinence can be assuaged using a new technique for vesicourethral anastomosis reconstruction during robot-assisted radical prostatectomy (RARP). This could significantly improve the quality of life of patients after RARP. More studies are needed to support our results.
Keywords: senioři; Robotic Surgical Procedures; Functional reconstruction; Robot-assisted radical prostatectomy; prostatektomie; Urethra; pánevní dno; Anastomotic Leak; netěsnost anastomózy; výsledek terapie; Single-Blind Method; Erectile function; Prostate cancer; Middle Aged; mužské pohlaví; nádory prostaty; jednoduchá slepá metoda; Urinary Bladder; Anastomosis; Continence; Pelvic Floor; Urinary Retention; močový měchýř; Postoperative Complications; kvalita života; uretra; Anastomosis, Surgical; Prostatic Neoplasms; Humans; Prostatectomy; inkontinence moči; anastomóza chirurgická; lidé středního věku; roboticky asistované výkony; Urinary Incontinence; zákroky plastické chirurgie; Quality of Life; Aged; Plastic Surgery Procedures; Treatment Outcome; pooperační komplikace; lidé; Male; retence moči